Phase II study of HCVIDD/MA in patients with newly diagnosed peripheral T‐cell lymphoma. (10th August 2015) - Chihara, Dai; Pro, Barbara; Loghavi, Sanam; Miranda, Roberto N.; Medeiros, L. Jeffrey; Fanale, Michelle A.; Hagemeister, Fredrick B.; Fayad, Luis E.; Romaguera, Jorge E.; Samaniego, Felipe; Neelapu, Sattva S.; Younes, Anas; et al.
Summary: A phase II study was performed to evaluate the efficacy of hyper‐fractionated cyclophosphamide, vincristine, pegylated liposomal doxorubicin and dexamethasone alternating with methotrexate/cytarabine (HCVIDD/MA) in patients with newly diagnosed peripheral T‐cell lymphoma (PTCL), excluding ALK‐positive anaplastic large cell lymphoma. Fifty‐three patients were enrolled. Treatment was planned for up to 8 cycles but only 9% of patients received more than 6 cycles due primarily to disease progression ( n = 13) or prolonged thrombocytopenia ( n = 12). The overall response rate was 66% with a complete response rate of 57%. Median progression‐free survival (PFS) was 7·5 months. With a median follow‐up of 7·6 years, 5‐year PFS and overall survival (OS) were 21% and 48%, respectively. The patients with extranodal Natural Killer‐cell lymphoma had a shorter PFS (median, 2·4 months) than other subtypes. Grade 3/4 anaemia, neutropenia and thrombocytopenia were observed in 66%, 74% and 79% of patients, respectively. Of note, 23% of patients discontinued therapy due to prolonged thrombocytopenia. In conclusion, HCVIDD/MA for the first‐line treatment of PTCL patients is associated with significant myelosuppression leading to poor treatment adherence, and the response and survival outcomes with this regimen are similar to standard CHOP. This study was registered atwww.clinicaltrials.gov as #NCT00290433.